2008
DOI: 10.1007/s00266-007-9107-5
|View full text |Cite
|
Sign up to set email alerts
|

Calf-Contouring Surgery of Gastrocnemius Hypertrophy: Selective Neurectomy of the Sural Nerve

Abstract: Generally, Asians tend to have obese calves that are shorter and thicker than those of Caucasians. The cause of the enlarged calves is either an excess of subcutaneous fat or calf muscular hypertrophy, but some patients have both conditions. These features are accentuated by the contraction of the calf muscles when patients stand in tiptoe position or wear high heels. In the case of calf muscular hypertrophy without excessive subcutaneous fat, manipulation of the calf muscle is an effective method for reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Most studies that have reported favorable gait analysis results after calf volume reduction procedures, however, have been based on selective gastrocnemius denervation procedures. 6,9 Iatrogenic damage of the tibial nerve to the soleus may have been involved during the initial procedure, which is in proximity to branches to the gastrocnemius. 14 All in all, mild gait difficulties were evident in both Silfverskiöld testYnegative cases, although a plantigrade foot was achieved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies that have reported favorable gait analysis results after calf volume reduction procedures, however, have been based on selective gastrocnemius denervation procedures. 6,9 Iatrogenic damage of the tibial nerve to the soleus may have been involved during the initial procedure, which is in proximity to branches to the gastrocnemius. 14 All in all, mild gait difficulties were evident in both Silfverskiöld testYnegative cases, although a plantigrade foot was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Published postoperative gait analysis results indeed show no significant functional deterioration after selective neurectomy. 6,9 Notable complications after selective neurectomy procedures are mostly transient, including temporary walking discomfort, transient numbness over the lateral ankle, and minor wound problems. 6,9 The possibility of iatrogenic nerve damage during selective neurectomy exists, as Hwang et al 14 reported the proximity of the common peroneal nerve to the tibial nerve entering the gastrocnemius muscle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations